PROBLEM BASED LEARNING-BERITA EKONOMI PACU MOTIVASI DAN PENGETAHUAN SISWA SMP NEGERI 1 KARANGTENGAH - Masroni (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
ABSTRACT Education in the modern era requires innovative approaches that can prepare the younger generation to face complex challenges in the future. SMP N 1 Karangtengah has a vision to create a stimulating and relevant learning environment to meet the needs of its students. Economic news as a learning source can serve as a bridge to integrate economic concepts into students' daily lives. The implementation of Problem Based Learning (PBL) is expected to provide a more engaging and meaningful learning experience, motivating students to actively understand the economic realities around them. This research aims to evaluate the effectiveness of PBL in enhancing students' motivation and understanding of economic news at SMP N 1 Karangtengah, Wonogiri, Central Java. The applied approach in this research is qualitative, focusing on the natural conditions of the object, where the researcher serves as the main instrument. The qualitative approach involves observing individuals in their natural environment, interacting with them, and attempting to understand their language and interpretations of the world around them. Learning outcomes improved after all students mastered the material, with the entire class achieving a 100% success rate and an average score of 90 after a daily quiz. Improvements were also evident in discipline and learning motivation through the use of technology-based media. The effectiveness of the implemented method by the researcher showed positive results, although it is emphasized that continuous improvement and review of the learning approach are necessary to ensure its sustainability in enhancing the quality of education at SMP N 1 Karangtengah.